Association of PTH and vitamin D-related genes with dental development in Brazilian children: a cross-sectional study - Isabela Ribeiro Madalena; Erika Calvano Küchler; Caio Luiz Bitencourt Reis; Mirian Aiko Nakane Matsumoto; Maria Bernadete Sasso Stuani; Thaís Vilalba Paniagua Machado do Nascimento; Christian Kirschneck; Flares Baratto-Filho; Maria Angélica Hueb de Menezes-Oliveira; César Penazzo Lepri (Brazilian Oral Research)
Abstract The aim was to evaluate the association between dental development (dental maturity) and genetic polymorphisms in PTH and genes involved in vitamin D synthesis in a cohort of Brazilian children. This retrospective cross-sectional study was performed on children receiving orthodontic treatment. Patients who had already undergone orthodontic treatment previously, those with syndromes, congenital anomalies, craniofacial deformities, and those with a previous history of dental trauma and bilateral agenesis/missing tooth/teeth were excluded. Panoramic radiographs were used for dental age evaluation according to the method proposed by Demirjian, Goldstein, and Tanner (1976). A delta [dental age minus chronological age (DA-CA)] was calculated to determine whether the patient's dental age was normal, delayed (negative values), or advanced (positive values). DNA isolated from buccal cells was used for genotyping genetic polymorphisms in PTH (rs694, rs307247, and rs6256), VDR (rs7975232), CYP27B1 (rs464653), and CYP24A1 (rs927650). A statistical analysis was performed and p<0.05 indicated statistical difference. A total of 79 orthodontic patients were included (44 (55.70%) girls and 35 (44.30%) boys). Demirjian, Goldstein, and Tanner's method (1976) overestimated the age of patients by 0.75 years. None of the genetic polymorphisms were associated with dental age (p>0.05). In conclusion, there is no association between genetic polymorphisms in PTH and genes involved in vitamin D synthesis and dental maturity.